2015
DOI: 10.1111/jop.12308
|View full text |Cite
|
Sign up to set email alerts
|

The potential of CD44 as a diagnostic and prognostic tool in oral cancer

Abstract: The CD44 family of molecules exists as a wide range of isoforms ubiquitously expressed on the surface of mammalian cells. The variation in patterns of CD44 expression on cancer cells has been widely studied in relation to their behaviour, and further interest has recently arisen in CD44 as a marker of the subfraction tumour cells acting as cancer stem cells in several types of tumours. This review focuses on the patterns of CD44 expression on the stem cell fraction of oral squamous cell carcinoma and on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 82 publications
0
24
0
3
Order By: Relevance
“…CD44s play an important role as tumor-promoting oncoproteins in early localized ampullary adenocarcinoma, while CD44 variants were correlated with advanced cancer and recurrent disease [4]. Recent studies have suggested that CD44 is probably a type of stem cell marker and useful as a diagnostic and prognostic tool in many cancers, including non-small cell lung cancer (NSCLC), breast cancer, gastric cancer, and oral cancer [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…CD44s play an important role as tumor-promoting oncoproteins in early localized ampullary adenocarcinoma, while CD44 variants were correlated with advanced cancer and recurrent disease [4]. Recent studies have suggested that CD44 is probably a type of stem cell marker and useful as a diagnostic and prognostic tool in many cancers, including non-small cell lung cancer (NSCLC), breast cancer, gastric cancer, and oral cancer [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been recognized that CSCs drives tumor progression and resistance to therapy, different stem cell markers have been investigated in solid tumors. An association among clinical pathological parameters, aggressiveness, and prognosis is expected in tumors with high expression of different stem cell markers, including CD44, NANOG, OCT4, and BMI1 . In this article, we have showed that there is a significant difference in the expression of CD44s , CD44v3 , NANOG , OCT4 , and BMI1 in tongue SCC in relation with nontumoral margins.…”
Section: Discussionmentioning
confidence: 65%
“…An association among clinical pathological parameters, aggressiveness, and prognosis is expected in tumors with high expression of different stem cell markers, including CD44, NANOG, OCT4, and BMI1. 3,23,24 In this article, we have showed that there is a significant difference in the expression of CD44s, CD44v3, NANOG, OCT4, and BMI1 in tongue SCC in relation with nontumoral margins. Additionally, CD44, NANOG, and OCT4 were positively associated with poor prognosis in patients with tongue SCC.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Ela medeia interações célula-célula e célulamatriz em grande parte por conta de sua afinidade com o ácido hialurônico, que é um constituinte da matriz extracelular. A CD44 também apresenta afinidade com outros ligantes, como a osteopontina e metaloproteinases da matriz (MMPs)(Cichy;Puré, 2003;Zhang et al, 2012;Emich et al, 2015).Pesquisas já mostraram a associação da expressão de CD44 com vias de sinalização que influenciam o crescimento, propagação e resistência do CEO(Al-Hajj et al, 2003;Prince et al, 2007;Zhang et al, 2012;Emich et al, 2015). Isso ocorre devido à interação da CD44 e do ácido hialurônico no domínio extracelular, promovendo vias de sinalização que desempenham papeis importantes na progressão tumoral de diversos tipos de câncer(Thapa;Wilson, 2016).Essa proteína já foi usada no isolamento e na caracterização das células tronco tumorais em carcinomas epidermóides de cabeça e pescoço.Prince et.al.…”
unclassified